Gas venting and late Quaternary sedimentation in the Persian (Arabian) Gulf - Uchupi, E.; Swift, S. A.; Ross, D. A. (Marine Geology, 1996)
High resolution 3.5 kHz echo sounding profiles and piston cores were used to reconstruct the microtopography and late Quaternary depositional history of the Persian Gulf. Perversive throughout the seafloor of the Gulf is an extensive network of pockmarks formed by seepages of thermogenic gas. These gas seeps and bottom water exiting the Gulf via the Strait of Hormuz are the most significant processes controlling present-day sedimentation in the region. Erosion by these seeps has been so intense in the Baiban Shelf in the Strait of Hormuz as to create a ''hoodoo'' like terrain on the outer shelf. The surfical geology of the Gulf documents a short lived transgression 29,400 to 22,800 years ago during the Wisconsin regression which began 125,000 years ago, the Wisconsin regressive maxima when sea level dropped to -120/-130 m about 21,000/20,000 years ago and the climate was dry and eolian and paralic sedimentation characterized the Gulf, the Holocene transgression 18,000 to 12,000 years ago when the climate was more humid than during the climax of the Wisconsin regression, a dry phase 12,000 to 9000 years ago when the Persian Gulf was a site of eolian and carbonate deposition, and the present sediment cycle during the last 9000 years under a more humid regime. It was during the present cycle that southeast trending marl lobes were deposited off Iran, Arabia acquired its hyper-arid climate about 3000 years ago and the Gulf attained its present configuration about 1000 years ago as a result of the construction of the Tigris Euphrates Delta at its head and tectonism and aggradation along its Arabian and Iranian flanks.
Tv774Times Cited:49Cited References Count:82